Out of the given choice, the equation represents
.
Answer: Option B
Explanation:
We know,
![\csc \theta=(1)/(\sin \theta)](https://img.qammunity.org/2020/formulas/mathematics/high-school/7cogxva5le5gf2xig8nujg4syaf4hsiufi.png)
![\sin \theta=(1)/(\csc \theta)](https://img.qammunity.org/2020/formulas/mathematics/high-school/u5yvvsanmc6morfpttbg35e0v1qqo3yiyp.png)
Given data:
![\csc \theta=(8)/(7)](https://img.qammunity.org/2020/formulas/mathematics/high-school/d2qc6y347zyj0ahkr9odtnzdp14kq5dwhk.png)
So, now sin theta can express as
![\sin \theta=\frac{7(\text { opposite })}{8(\text { Hypotenuse })}](https://img.qammunity.org/2020/formulas/mathematics/high-school/bzimz71grvd18kfmhpoo61x9k6749epdke.png)
Sin theta defined by the ratio of opposite to the hypotenuse. In general, the adjacent can be calculated by,
![\text {(opposite) }^(2)+(\text { adjacent })^(2)=(\text {Hypotenuse})^(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/ia4aqk5ulu0236eycx13mbvp27ikj32z84.png)
![7^(2)+(\text { adjacent })^(2)=8^(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/hk635m6po6k2xh3lj2ncu7gzspo2pminhd.png)
![(\text {adjacent})^(2)=8^(2)-7^(2)=64-49=15](https://img.qammunity.org/2020/formulas/mathematics/high-school/nvtfni0rw950y7wsgmcl15lw104t0ylhb6.png)
Taking square root, we get
![\text { adjacent }=√(15)](https://img.qammunity.org/2020/formulas/mathematics/high-school/bn24ln9cit3qif7n64n943gh9m9ipxu9pm.png)
Also, we know the formula for cot theta,
![\cot \theta=(1)/(\tan \theta)=(1)/(\left((\sin \theta)/(\cos \theta)\right))=(\cos \theta)/(\sin \theta)](https://img.qammunity.org/2020/formulas/mathematics/high-school/q92fup49bp6fl47unray66pqzav5jo5vio.png)
Cos theta denoted as the ratio of adjacent to the hypotenuse.
![\cos \theta=\frac{√(15)(\text {Adjacent})}{8(\text {Hypotenuse})}](https://img.qammunity.org/2020/formulas/mathematics/high-school/nh8ch8h1rm4va5r8v5cdkb2njre9pxj5e2.png)
Therefore, find now as below,
![\cot \theta=(\left((√(15))/(8)\right))/(\left((7)/(8)\right))=(√(15))/(8) * (8)/(7)=(√(15))/(7)](https://img.qammunity.org/2020/formulas/mathematics/high-school/u2q1a3n6q4e04ze1f1d8sh0w2ukfc9t8i7.png)